The bearing of personalistic Filipino political culture on people's perception on the services of local government officals in Poblacion, Tubungan, Iloilo. - Sumido, Analyn C; Imperial, Noelle G. (2003.)
The study was undertaken to find out the bearing of personalistic political culture on people's perception on the services of local government officials in Poblacion, Tubungan. The study specifically aimed to find out whether the people of poblacion, Tubungan practice a personalistic political culture; To know how the people perceived the services of elected government officials; To analyze whether the practice affected their perception of government official's services. The political culture that the study focused on were categorized into: primacy of kinship ties, utang na loob, and use of political connections. (p)The respondents of this study were the 100 randomly selected residents of Poblacion, Tubungan. They are of voting age and registered during the 1998 elections. A stratified sampling was used to get the representatives from the three zones comprising the Poblacion: 41 were from zone 1, 28 from zone II, and 31 from zone III. (p)An interview schedule was used to gather data for this study. The descriptive statistical tool used to analyze data was percentage rating. (p)Findings of the study were: (1)Majority of the people in the Poblacion practice personalistic political culture, specifically utang na loob and use of political connections in dealing with their elected officials. The percentage of those who give importance to family and kinship ties, however, is lesser compared to those who do not. The people also practice compadrazgo personally go to official's house when asking for services and believe in "backer system". (2)Majority of the people found their government officials' services satisfactory. The services that they are aware of include: health services, water facilities services, electrical facilities services, maintenance of peace and order, establishment of public schools, recreational services, helping of the poor, implementation of laws, implementation of social welfare programs, formulation of ordinances, personally attending to community's problem, environmental services, emergency assistance, literacy programs, putting up infrastructures and livelihood projects. (3)There is greater percentage from those who practice personalistic political culture who find their government officials' services satisfactory compare to the percentage of those who do not practice. The practice of personalistic politcal culture, therfore, has a bearing on people's perception on the services of the government officials. (p)Based on the conclusion, the following recommendations were forwarded: (1)Students of political science should conduct more relevant researhes about Filipino political culture to understand more the dynamics of politics in rural Philippines. (2)Students are also encouraged to use statistical tools to establish stronger relationship between political culture and people's perception of their government officials. (3)The government officials of Tubungan should be responsive to the people's needs and complaints regarding their performance. The services they offer should be available to all constituents regardless of their connection to them or their class status. (4)The people of Tubungan should also be more aware and vigilant of their officials' performance and the services they offer. They shpuld participate in any programs or activities in the municipality to increase their awareness and efficacy.
Research Paper (Undergraduate, Bachelor of Arts in Political Science-Management) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Local Government Officials -- Tubungan, Iloilo